Evolution of nuptiality and its effect on fertility - Fouzia Beladjal; Karim Chadou (Social Empowerment Journal, 2021)
The phenomenon of marriage has been linked to customs and traditions through the prevailing social practices and values, but the transformation that this phenomenon is witnessing is only the result of the clear impact of the social, cultural and economic changes that most societies undergo. In turn, the phenomenon of fertility has been linked to the one of marriage, and any effect on one of them does necessarily affect the other, and this is what our study confirmed by tracking Algerian statistics across different time periods. This becomes apparent through the development of the first marriage age from one period to another, in addition to reaching a conclusion that there is an inverse relationship between the average age of the first marriage and the age difference between the spouses, as the higher the average age of the first marriage, the smaller the age difference between the spouses.Our study indicated that we can consider the average age of first marriage as one of the basic determinants of fertility and a major factor in fertility levels, as it directly affects the birth numbers, whereas, the higher the age at the first marriage, the lower the average number of births.